Designing a Mobile-Based Digital Financial Application to Enhance Financial Access for Indonesian Communities - Afkar, Muhammad Agha (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
The issue of financial access remains a significant challenge in Indonesia, particularly in remote and underdeveloped regions. Digital financial services offer a promising solution to accelerate and simplify financial access; however, many individuals are still unable to fully utilize these services. This research aims to design a mobile-based digital financial application that can enhance financial access for Indonesians in a simple, fast, and efficient manner. The study employs both qualitative and quantitative approaches, including literature reviews, interviews, surveys, and application design modeling. These methodologies will provide a comprehensive understanding of the barriers and facilitators to digital financial access. The results of this research will inform the design and development of a digital financial application tailored to the needs and preferences of users. The anticipated outcome is a digital financial application that not only facilitates financial transactions but also improves financial literacy and broadens access to digital financial services. This application is expected to simplify everyday financial activities such as bill payments, money transfers, and the purchase of financial products. In the long term, the application aims to assist Indonesians in accelerating economic development by easing access to digital financial services, reducing reliance on conventional financial services that are often difficult to access, and providing a modern, user-friendly alternative. Moreover, the application seeks to address the low level of financial literacy by incorporating educational features that empower users to make informed financial decisions. By doing so, it contributes to sustainable economic growth and financial inclusion across diverse Indonesian communities.